2022
DOI: 10.1039/d2cc00206j
|View full text |Cite
|
Sign up to set email alerts
|

Nitrative bicyclization of 1,7-diynes for accessing skeletally diverse tricyclic pyrroles

Abstract: A novel metal-free nitrative bicyclization of 1,7-diynes with tBuONO in the presence of H2O is reported, producing three types of skeletally diverse tricyclic pyrroles such as pyrrolo[3,4-c]quinolines, chromeno[3,4-c]pyrroles and benzo[e]isoindoles...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Samanta et al reported the synthesis of 2-(2,4-dihydrochromeno[3,4- c ]pyrrol-1-yl)acetates 8 from 3-(3-formyl-2 H -chromen-4-yl)acrylates 7 by treatment with hydroxylamine hydrochloride, amino alcohols or sodium azide [ 19 , 20 ]. Recently, a metal-free method for the synthesis of chromeno[3,4- c ]pyrroles 9 based on nitrative cyclization of the corresponding 1,7-diynes with tert -butyl nitrite in the presence of water has been developed [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Samanta et al reported the synthesis of 2-(2,4-dihydrochromeno[3,4- c ]pyrrol-1-yl)acetates 8 from 3-(3-formyl-2 H -chromen-4-yl)acrylates 7 by treatment with hydroxylamine hydrochloride, amino alcohols or sodium azide [ 19 , 20 ]. Recently, a metal-free method for the synthesis of chromeno[3,4- c ]pyrroles 9 based on nitrative cyclization of the corresponding 1,7-diynes with tert -butyl nitrite in the presence of water has been developed [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, our group has been engaging in the development of radicaltriggered annulation reactions of 1,n-diynes that can render easy access to some important cyclic molecules for downstream studies in chemical biology and pharmaceutical chemistry. [13] During this project, we reasoned that sulfonyl radicals derived from aryl diazonium tetrafluoroborates and DABSO under thermolytic conditions could regioselectively add to heteroatom-linked 1,7-diynes, followed by 6-exo-dig cyclization and annulative SO 2 insertion to produce tricyclic sulfones. Such an approach enables the realization of exocyclic and annulative double SO 2 insertion.…”
mentioning
confidence: 99%